Digital Blood Flow In Systemic Lupus Erythematosus By Photoplethysmography - Ghosh Sanjay; Biswas Abani (Wolters Kluwer Medknow Publications, 2002)
Digital vascular status in 10 patients of systemic lupus erythematous (SLE) suffering for 1 to 5 years and 5 control (normal) subjects was assessed by a highly sensitive, non-invasive technique called photoplethysmography (PPG). Six patients (Group A) showed clinical sign. PPG recordings were done by applying the PPG probe serially to the distal phalanges of all the digits of four limbs with Velcro-strap at an ambient temperature of 27 to 31C and humidity 60 to 65% Diminished capillary flow. On average, 12 digits (60%) in Group A and 8 digits (40%) in group B patients showed reduced blood circulation. Degree of vascular impairment had no bearing upon the duration of the disease. The PPG has objectively shown digital vascular impairment in all SLE patients having no correlation with the extent of clinical manifestations and the duration of the disease.